STRATEGI PEMBANGUNAN ILMU PENGETAHUAN MELALUI LITERASI SAINS - Sinaga, Yenniwati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
The development of science and technology in Indonesia continues to grow. Competition is increasingly fierce and society is required to be able to compete in facing challenges in the era of globalization. The international world will recognize the nation's progress if the majority of society is able to master, utilize and develop science and technology.This article discusses the development of science. One strategy that can be used to build science is to increase scientific literacy. Scientific literacy is not only knowledge and understanding of scientific concepts and processes, but is also directed at how a person can make decisions and participate in social life, culture and economic growth